Relationship Of Self-Control With Student Academic Procrastination - Desta Mandasari; Herman Nirwana (Jurnal Neo Konseling, 2019)
This study aims to (1) describe student academic procrastination, (2) describe student self-control, and  (3) examine the relationship of self-control with student academic procrastination. This type of research is quantitative research using a descriptive and correlational analysis approach. The population in this study were students of class VII, VIII, and IX SMP N 12 Padang and the amount of samples was 270 students taken using proportional stratified random techniques. This study uses two data analysis techniques, descriptive analysis and correlational analysis. Descriptive analysis is using the percentage formula. While correlational analysis uses the product moment correlation formula and the calculation is assisted by using the SPSS version 20.0 for Windows. The results of the study showed (1) the level of academic procrastination in Padang SMP N 12 students in general was in the high category, (2) the level of self-control of SMP N 12 Padang students was generally in the low category, and (3) there was a significant relationship between self -control with academic procrastination students of SMP N 12 Padang with a correlation coefficient of -0.141 and a significance level of 0.020.